Imagining Historical Imagology: Possibilities and Perspectives of Transdisciplinary/Translational Epistemology - Blažević, Zrinka (Array, 2012)
According to the dominant trend marked by the global exchange of theoretical paradigms, this paper is aimed at examining possibilities of the epistemological constitution of the historical imagology as a transdisciplinary and translational research practice. Defining images as interferrential configuration of the mental images, representations and practice patterns within certain socio-historical context, the main focus will be put on the interpretative and explanatory landmarks stemmed from neurobiological and psychoanalitical theories of the self, discourse analysis and praxeological theories. Final part of the paper will highlight some theoretical impulses of gender and postcolonial studies for examining complex dynamics of the process of appropriation, modification and distribution of auto, hetero- and metaimages or, generally, for understanding insolvable dialectics of the mutual constitution of identity and alterity, structurally determined by the asimmetrical relations of economic, cultural and social power.